2022
DOI: 10.3390/jcm11154399
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Liver Biopsy for Undefined Nodules in Patients under Surveillance for Hepatocellular Carcinoma: Is Biopsy Really a Useful Tool?

Abstract: The aim of the present study is to determine the feasibility of biopsy for atypical liver nodules in patients under surveillance for hepatocellular carcinoma (HCC), assessing which factors influence the decision to perform it. Methods: A total of 128 atypical liver nodules in 108 patients under surveillance for HCC, who underwent CT between September 2018 and September 2019, were included. All the images were saved digitally (on CD-ROM) and the two most representative images in the arterial and delayed phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Owing to the characteristic imaging patterns of HCC, most patients are diagnosed before surgery on the basis of radiologic findings detected during enhanced computed tomography (CT) or enhanced magnetic resonance imaging (MRI) examinations, for example (2,3). Moreover, the tendency of uncontrollable hemorrhage, the possibility of biopsy-related tumor metastasis, and the likelihood of false negative results due to the size and location of nodules mean that imaging techniques are safer and more convenient presurgical procedures for the diagnosis and evaluation of HCC than other diagnostic methods such as needle biopsy (4).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the characteristic imaging patterns of HCC, most patients are diagnosed before surgery on the basis of radiologic findings detected during enhanced computed tomography (CT) or enhanced magnetic resonance imaging (MRI) examinations, for example (2,3). Moreover, the tendency of uncontrollable hemorrhage, the possibility of biopsy-related tumor metastasis, and the likelihood of false negative results due to the size and location of nodules mean that imaging techniques are safer and more convenient presurgical procedures for the diagnosis and evaluation of HCC than other diagnostic methods such as needle biopsy (4).…”
Section: Introductionmentioning
confidence: 99%
“…The definitions used for defining limited visualization in aMRI were heterogenous, and a consensus, standardized definition is required. We were unable to investigate the effect of tumour size on visualization quality due to a lack of data, although previous studies have demonstrated reduced sensitivity of imaging techniques for the detection of small lesions from 10 to 20 mm, especially for lesions less than 10 mm [5153]. Finally, there were insufficient studies to perform subgroup analysis among patients without cirrhosis and by aetiology.…”
Section: Discussionmentioning
confidence: 98%
“…Intra-nodular vascular alterations occur during hepatocarcinogenesis, with a progressive reduction in the portal blood supply and a concomitant rise in the arterial flow delivered by the so-called “unpaired” arteries. The arterial phase hyperenhancement (APHE) and wash-out of the contrast medium in the portal and/or delayed phases are the classic radiologic characteristics of HCC, which are caused by vascular derangement [ 63 ]. The typical radiographic characteristics of “wash-in” and “wash-out” are adequate for recognizing HCC in nodules larger than 10 mm, and a biopsy should only be considered for nodules with atypical imaging characteristics [ 64 , 65 ].…”
Section: Diagnosis Of Precancerous Lesions Of Hccmentioning
confidence: 99%